Implementing Project-Based Learning in the Independent Curriculum: Insights from Secondary Level Teachers’ Perspectives - Phunyal , Balkrishna (Tribhuvan University Journal, 2025)
This research was conducted to observe the perception of teachers about Project Based Learning (PBL) as a method of teaching in the Independent Curriculum. It focused on three key areas, the knowledge of the teachers on PBL concepts, their classroom practices of implementing PBL and their perception of the effects of PBL on student motivation and student learning outcomes. Quantitative research design was applied as a descriptive one (102 teachers were selected with the help of purposive sampling); these teachers were active participants of the process of the Independent Curriculum implementation. The structured Likert scale questionnaire survey was used to gather the data and included sections on conceptual understanding, classroom application, and perceived student impact. Spreadsheet tools in WPS office were used in the descriptive statistical analysis. The results show that educators tend to have a positive attitude of PBL, and they have a high level of theoretical understanding of the principles. The majority of teachers admitted that it is efficient at enhancing the collaboration, motivation, and thinking among students. Nevertheless, the outcomes also show the disconnect between the theoretical knowledge and the reality. Specifically, educators described difficulties associated with the adoption of interdisciplinary projects. The research finds that teachers are conceptually ready to implement PBL, but specific professional mattering is necessary to make the implementation more practical and help the successful attainment of the goals provided by the Independent Curriculum.